Feeding hydroalcoholic extract powder of Lepidium meyenii (maca) increases serum testosterone concentration and enhances steroidogenic ability of Leydig cells in male rats. (14th July 2015) - Ohta, Y.; Yoshida, K.; Kamiya, S.; Kawate, N.; Takahashi, M.; Inaba, T.; Hatoya, S.; Morii, H.; Takahashi, K.; Ito, M.; Ogawa, H.; Tamada, H.
Summary: Although Lepidium meyenii (maca), a plant growing in Peru's central Andes, has been traditionally used for enhancing fertility and reproductive performance in domestic animals and human beings, effects of maca on reproductive organs are still unclear. This study examined whether feeding the hydroalcoholic extract powder of maca for 6 weeks affects weight of the reproductive organs, serum concentrations of testosterone and luteinising hormone (LH), number and cytoplasmic area of immunohistochemically stained Leydig cells, and steroidogenesis of cultured Leydig cells in 8‐week‐old male rats. Feeding the extract powder increased weight of seminal vesicles, serum testosterone level and cytoplasmic area of Leydig cells when compared with controls. Weight of prostate gland, serum LH concentration and number of Leydig cells were not affected by the maca treatment. The testosterone production by Leydig cells significantly increased when cultured with 22 R ‐hydroxycholesterol or pregnenolone and tended to increase when cultured with hCG by feeding the extract powder. The results show that feeding the hydroalcoholic extract powder of maca for 6 weeks increases serum testosterone concentration associated with seminal vesicle stimulation in male rats, and this increase in testosterone level may be related to the enhanced ability of testosterone production by Leydig cells especially in the metabolic process following cholesterol.